Desmoid Fibromatosis Presenting as An Omental Mass: A Case Report - Basim, Aljalabneh; Patrick, Shenjere; ST, O'Dwyer (Archives of Clinical and Medical Case Reports, 2021)
Intra-abdominal desmoid fibromatosis (IADF) is a rare condition, comprising 8-15% of all presentations of desmoid fibromatosis (DF), most commonly arising from the small bowel mesentery. We report the case of a 34 year old male, who presented with a 7.4 x 6.5 cm right iliac fossa mass arising from the omentum. Percutaneous biopsy was inconclusive and the working diagnosis was desmoplastic small round cell cancer of appendiceal or urachal origin. He underwent a diagnostic debulking procedure; a dominant omental mass was removed and 2-3 mm peritoneal nodules on the distal small bowel mesentery and a bulky mass around the root of the superior mesenteric vessels were noted. Histopathological, immunohistochemical and gene mutation analysis confirmed IADF as the definitive diagnosis. We review the literature of this rare presentation and discuss challenges in diagnosis and subcategorization of DF.